The Relevance of The Philosophy of Education as a System and Its Relationship with Philosophy and Islam In The Formation of National Character - Noerafifah, Dinna Widya; Chusni, Muhammad Minan (KOLABORASI: Journal of Multidisciplinary, 2024)
The condition of character crisis is a serious threat to the values ​​of national character. Education plays an important role in the formation of national character. This study aims to understand the relationship between the philosophy of education as a system to the formation of national character, the relationship between the philosophy of education and philosophy in the formation of national character, and the relationship between the philosophy of education and Islam in the formation of national character. The method used in this study is the literature study method which involves collecting and analyzing data from several scientific journals, articles, and reports. The philosophy of education can be a system and help implement Islamic values ​​in the education process to form the character of the nation. In addition, education plays an important role in forming the character of the nation through various disciplines such as character education, citizenship education, history learning, Islamic religious education obtained from Islamic boarding schools, and entrepreneurship education.